Large-scale relief of the Slovak Karst and Aggtelek Karst (Gömör-Torna/Gemer-Turňa Karst) - a DEM-based study - Tamás Telbisz (Hungarian Geographical Bulletin, 2011)
The surface of the Gömör–Torna/Gemer–Turňa Karst (GTK) was largely formed by Pannonian or Pliocene pediplanation. Although this surface has been dissected by subsequent tectonic and fluvial processes, the present karst plateaus still preserve large pieces of this once homogeneous surface. GIS-based statistical methods have been used to calculate exact aspects and slopes of the relict surfaces using the Shutt le Radar Topography Mission digital terrain model (SRTM DTM). Topographic swath profiles proved to be especially useful in the analysis, because top levels of the relief are marked in these profiles thus facilitating the identification and quantitative characterisation of these relict surfaces. Analysis results show that a general 1° slope is valid for most of the GTK. This very low slope angle is typical for particular karst plateaus as well as for long north to south cross-sections covering the whole karst area. Based on the smooth-filtered DTM the largest, most homogeneous surfaces (Plešivská plateau, Silická plateau) have a dominant south–south-western aspect, many other plateaus have southern aspect, whereas peripheral plateaus slope towards the margins. Uplift resulted in a uniform tilt in the western part of the area including the Slovenské rudohorie (Slovak Ore Mts.) found north of the GTK, while in the central and eastern zones the blocks uplift ed to different elevations and their tilts are more varied. In these zones, the Slovenské rudohorie are above the elevation trend of GTK, therefore a fault step also separates these morphological units. The origin of Slaná (Sajó) and Štítnik (Csetnek) valleys (east and west of Plešivská plateau) is debatable in the literature. Taking into consideration the good fit of topographic trends on opposite sides of valleys, vertical faulting can be excluded, therefore superimposition/antecedence could be the dominant process although tectonic preformation certainly had some influence in case of Štítnik valley. Before the tectonic uplift of GTK or in its early phase, water courses fl owing in north to south direction existed in the central parts. Traces of these flows are observable in the present relief around Jablonovské sedlo (saddle) and Derenk.